2009
DOI: 10.1007/s11282-009-0029-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of trabecular bone healing by fractal analysis and digital subtraction radiography on digitized panoramic radiographs: a preliminary study

Abstract: Objectives We have evaluated radiographic changes in mandibular bone texture before and after surgical therapies using fractal analysis and digital subtraction radiography (DSR). Materials and methods Preoperative and postoperative panoramic radiographs of 10 patients were acquired and converted into digital format. The procedures for calculating the fractal dimension (FD) were performed using Image J 1.38x software, and the mean gray values (MGVs) for digital subtraction were implemented using newly developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…27 In general, FD has been used in several other dental specialties such as endodontics, 49,55,56 orthodontics 67 and oral and maxillofacial surgery. 5,21,25 Several studies can be conducted with FA to assess the patterns of bone complexity. A tool that calculates FD should be incorporated into the imaging program to facilitate access and allow the practitioner to further explore this methodology.…”
Section: Discussionmentioning
confidence: 99%
“…27 In general, FD has been used in several other dental specialties such as endodontics, 49,55,56 orthodontics 67 and oral and maxillofacial surgery. 5,21,25 Several studies can be conducted with FA to assess the patterns of bone complexity. A tool that calculates FD should be incorporated into the imaging program to facilitate access and allow the practitioner to further explore this methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Texture feature analysis was also applied to evaluation of the bone structure affected by osteoporosis [23][24][25], and similar techniques were used to characterize periapical bone loss [26][27][28][29], periapical bone healing [30][31][32][33], and focal periapical lesions [34,35]. Other research has focused on evaluation of the jaws [36] and cases in which sex-dependent structural differences in the jaw bone are visible [37].…”
Section: Related Workmentioning
confidence: 99%
“…FD after 1 and 6 months decreased compared to FD before surgery, but then increased at 12 months. Koca et al [33] found an increase in FD measured 18 months after surgery with respect to the preoperative value. This was done on 10 patients who were operated to treat different sorts of cysts.…”
Section: Surgerymentioning
confidence: 91%